Asymmetric Information, Bank Lending, and Implicit Contracts: A Stylized Model of Customer Relationships - SHARPE, STEVEN A. (Journal of Finance, 1990)
ABSTRACT Customer relationships arise between banks and firms because, in the process of lending, a bank learns more than others about its own customers. This information asymmetry allows lenders to capture some of the rents generated by their older customers; competition thus drives banks to lend to new firms at interest rates which initially generate expected losses. As a result, the allocation of capital is shifted toward lower quality and inexperienced firms. This inefficiency is eliminated if complete contingent contracts are written or, when this is costly, if banks can make nonbinding commitments that, in equilibrium, are backed by reputation.